Small-scale variation of the horizontal and vertical structure of macrobenthic communities in a coastal lagoon of the southwestern Atlantic (INNOTEC, 2019)
: Rocha Lagoon is part of the chain of coastal lagoons extended along Uruguayan Atlantic coast, which continues through southern Brazil. It presents a complex ecological dynamic due to the marine-brackish gradient. The benthic macrofauna is an important component of these estuarine environments which is affected by its complex dynamics. In the present work, we analysed how sand-tongues (sand accumulation perpendicular to the sandbar) affects the macrobenthic fauna. We stablished the relationship between macrobenthos and environmental variables on a vertical (different depths within the sediment) and horizontal (both sides of the sand-tongues) scales, as well as evaluating the influence of the distance to the marine intrusion. In all the sampling points, the environmental parameters (organic matter, total phosphorus, dissolved oxygen, chlorophyll-aand phaeopigments) showed a vertical trend (decreasing towards the bottom), and the macrobenthos responded to these changes. The dominance of Heleobia australis, Nephtys fluviatilisand Heteromastus similiswas observed in different sampling points and sediment depths. There is a spatial partition of resources reflected by these changes in dominance, while the vertical distribution of the macrobenthic community responds to both biotic and environmental conditions.
Keywords: estuaries; Rocha Lagoon; spatial scales; transitional waters; vertical distribution